Aloe QDM complex enhances specific cytotoxic T lymphocyte killing in vivo in metabolic disease mice. Issue 3 (4th March 2017) - Lee, Youngjoo; Kim, Jiyeon; An, Jinho; Lee, Heetae; Kong, Hyunseok; Song, Youngcheon; Shin, Eunju; Do, Seon-Gil; Lee, Chong-Kil; Kim, Kyungjae
Abstract: We developed spontaneous diet-induced metabolic disease in mice by feeding them a high-fat diet for 23 weeks and administered Aloe QDM complex for 16 weeks to examine its restorative effect on immune disorders and metabolic syndrome. A series of immune functional assays indicated Aloe QDM complex enhanced lymphocyte proliferation and antigen-specific immunity as determined by the restored functions of cytotoxic T lymphocytes (CTL) and IgG production. The elevated serum TNF-α level was also regulated by Aloe QDM complex treatment, which suggested its complex therapeutic potential. As for metabolic phenotypes, oral administration of Aloe QDM complex significantly improved diabetic symptoms, including high fasting glucose levels and glucose tolerance, and distinctly alleviated lipid accumulation in adipose and hepatic tissue. The simultaneous restoration of Aloe QDM complex on metabolic syndrome and host immune dysfunction, especially on the specific CTL killing was first elucidated in our study. Abstract : :